Regulation of KLF12 by microRNA‐20b and microRNA‐106a in cystogenesis. Issue 7 (16th February 2018) - Shin, Yubin; Kim, Do Yeon; Ko, Je Yeong; Woo, Yu Mi; Park, Jong Hoon
Abstract : Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common inherited disorders. ADPKD is caused by mutations in the gene encoding either polycystic kidney disease 1 (PKD1) or polycystic kidney disease 2 (PKD2). Patients with ADPKD show progressive growth of cystic fluid‐filled renal cysts. Here, we used Pkd2 f/f control mice and Pkd2 f/f :HoxB7‐Cre experimental mice, which are bred to have a conditional deletion of Pkd2 in the collecting ducts, and analyzed the expression pattern of microRNAs (miRNAs) of kidney tissues from Pkd2 f/f and Pkd2 f/f :HoxB7‐Cre mice. Decreased expression of miR‐20b‐5p and miR‐106a‐5p in Pkd2 f/f :HoxB7‐Cre mice compared to that in Pkd2 f/f mice was observed. These miRNAs target Klf12 (Kriippel‐like factor 12), which has low expression in kidney tissues of Pkd2 f/f mice; however, its expression is enhanced in Pkd2 f/f :HoxB7‐Cre mice over time. Moreover, miR‐20b‐5p and miR‐106a‐5p directly target Klf12 mRNA by binding to the 3′‐UTR of Klf12.ln addition, human and mouse cell lines exhibit similar patterns. These findings were also consistent with the data from Pkd2 knockout mouse embryonic fibroblasts. Furthermore, direct and indirect knockdown of Klf12 slows cyst growth and cell proliferation in mouse inner medullary collecting duct cells. Taken together, we suggest that the induction of miR‐20b‐5p or miR‐106a‐5p or the down‐regulation of KLF12 could be used as potential novel therapies for inhibiting cyst growth in patients with ADPKD.—Shin, Y., Kim, D.Y., Ko, J.Y., Woo, Y. M., Park, J. H. Regulation of KLF12 by microRNA‐20b and microRNA‐106a in cystogenesis. FASEB J. 32, 3574–3582 (2018). www.fasebj.org